Role of media and independent directors in corporate transparency and disclosure: evidence from an emerging economy. Issue 5 (16th April 2018) - Zaman, Rashid; Bahadar, Stephen; Kayani, Umar Nawaz; Arslan, Muhammad
Abstract : Purpose: The purpose of this paper is to examine the impact of corporate governance, with particular reference to the role of independent directors on boards and audit committees, and media coverage on corporate transparency and disclosure. In addition, the paper also investigates the role of the media on independent directors' behaviours towards corporate transparency and disclosure. Design/methodology/approach: The paper uses the well-developed two-step system generalised method of moments approach on a sample of 99 Pakistan stock exchange (PSX) listed financial firms over the period 2007-2012. Findings: The empirical analysis shows that media and independent directors on audit committees play a significant positive role in line with agenda setting and agency theories in promoting corporate transparency and disclosure. On the contrary, the boards' independent directors are risk-averse and hold the information to protect their reputation. Nevertheless, the study does not find any significant influence of media coverage on independent directors' behaviours in promoting corporate transparency and disclosure. Practical implications: The findings provide some useful insight into cost benefits analysis of media coverage towards an understanding of independent directors' behaviours for promoting transparency and disclosure in financial sector. Moreover, the study findings can be useful for both shareholders and stakeholders in taking decisions about firm activities. Originality/value: To the best of the authors' knowledge, this is the first study that proposed and tested a multi-level framework for corporate transparency and disclosure practices. In addition, this study is also among the very few studies that use financial sectors as a sample, in particular, and media coverage, specifically, thus adding some value to the limited literature.